PARTISIPASI MASYARAKAT DALAM MENGELOLA SAMPAH RUMAH TANGGA UNTUK MENINGKATKAN KUALITAS KESEHATAN DI KAMPUNG SEKEAWI RT 001 RW 002 - Herianto, Herianto; Nandang Rukanda, Nandang Rukanda (IKIP Siliwangi, 2024)
Waste is waste that results from a production process, both domestic (household) and industrial. In Law No. 18 of 2008 concerning Waste Management, it is stated that waste is the remains of daily human activities or natural processes in solid or semi-solid form in the form of biodegradable or non-degradable organic or inorganic substances which are deemed no longer useful and are thrown away. to the environment. The bad habit of throwing rubbish carelessly seems to be familiar, even as if it is used to it. Society is the largest human group that has the same habits, traditions, attitudes and feelings of unity. Society is also the main key to the waste problem. As stated by Environmental Health, it is one of the health efforts to create a healthy environmental quality, both physical, chemical, biological and social, which enables everyone to achieve the highest level of health. Management of household waste and similar household waste consists of reducing waste and handling waste. Waste reduction includes several activities, including limiting waste generation, recycling waste, and reusing waste. There are several ways to create a clean environment: (1) Community (2) Garbage (3) Health quality